Role of R&D investments and air quality in green governance efficiency. Issue 1 (31st December 2022) - Zhao, Linhai; Taghizadeh-Hesary, Farhad
Abstract: This article measures the impact of R&D investment and carbon dioxide (CO2 ) emission of the Shanghai and Shenzhen stock market listed companies on the green governance efficiency (G.G.E.). An econometric analysis based on the data from 2015 to 2019 is used to measure the impact. The study's findings reveal that research and development (R&D) investments significantly boost G.G.E. On the other hand, CO2 emission and energy intensity reduce G.G.E. The study results show that the listed companies' performance would have a significant role in achieving the Chinese government's carbon neutrality goal. The study provides policy recommendations to promote green governance performance in China and other developing countries.